2021
DOI: 10.1001/jamanetworkopen.2021.16240
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Apatinib Plus Chemotherapy as Neoadjuvant Treatment for Locally Advanced Gastric Cancer

Abstract: IMPORTANCE Apatinib is a novel treatment option for chemotherapy-refractory advanced gastric cancer (GC), but it has not been evaluated in patients with locally advanced GC.OBJECTIVE To investigate the effectiveness and safety of apatinib combined with S-1 plus oxaliplatin (SOX) as a neoadjuvant treatment for locally advanced GC. DESIGN, SETTING, AND PARTICIPANTSThis multicenter, prospective, single-group, open-label, phase 2 nonrandomized controlled trial was conducted in 10 centers in southern China. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
2
30
1
Order By: Relevance
“…There were no grade 4 adverse events or preoperative death observed. Compared with patients who did not experience adverse events, patients with grade 3 adverse events had a significantly lower average number of preoperative cycles, indicating that the incidence of adverse events was not related to the cumulative exposure to the drug ( 43 ). Results from clinical trials demonstrated that neoadjuvant chemotherapy combined with apatinib achieved a better survival benefit in the unresectable advanced gastric cancer with acceptable safety.…”
Section: Clinical Efficacy In Advanced Gastric Cancermentioning
confidence: 99%
“…There were no grade 4 adverse events or preoperative death observed. Compared with patients who did not experience adverse events, patients with grade 3 adverse events had a significantly lower average number of preoperative cycles, indicating that the incidence of adverse events was not related to the cumulative exposure to the drug ( 43 ). Results from clinical trials demonstrated that neoadjuvant chemotherapy combined with apatinib achieved a better survival benefit in the unresectable advanced gastric cancer with acceptable safety.…”
Section: Clinical Efficacy In Advanced Gastric Cancermentioning
confidence: 99%
“…To our knowledge, this is the first study to evaluate the concomitant use of a VEGFR TKI and XELOX for patients with locally advanced adenocarcinoma of the stomach or GEJ in the neoadjuvant setting. Some similar studies also investigated neoadjuvant apatinib combined with chemotherapy (S-1 and oxaliplatin) but only reported short-term efficacy (R0 resection rate [ 30 ] or pRR [ 31 ]). Our study was first to report the survival outcomes in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Zheng et al which enrolled 29 patients with LAGC, the ORR was 79.3% and pRR was 37.9% [ 31 ]. In another study by Lin et al which enrolled 48 patients with LAGC, the ORR was 75% and pRR was 25% [ 30 ]. In the present study, the ORR was 78.1% and pRR was 34.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib is a new tyrosine kinase inhibitor that exhibits significant antitumor activity in several solid tumors including HCC and gastric cancer by targeting VEGF receptor-2 (VEGFR-2) to inhibit tumor angiogenesis. 50 , 51 Fibrosis promotes angiogenesis by upregulating the expression of VEGF and its receptor VEGFR-2; 30 high ROS also increases the secretion of VEGF. 52 Autocrine VEGF-induced VEGFR2 overexpression can enhance the treatment efficiency of apatinib in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%